Tarjuma-yi manẓūm-i waṣiyyat-i Imām ʿAlī (ʿalayhi al-salām) bih Imām Ḥusayn (ʿalayhi al-salām) : Kuhantarīn tarjuma-yi manẓūm-i Fārsī az kalām-i ʿAlawī - Ghaznawī, Sayyid Ḥasan, (Miras Maktoob, ISBN: 9789004365452., 2019)
In Shīʿī literature, there exist several texts containing the last will ( waṣiyya ) of ʿAlī b. Abī Ṭālib, son-in-law of the Prophet and, in Shīʿism, his rightful successor. These last wishes were addressed to his sons Ḥasan and Ḥusayn and to the Muslim community at large. Transmitted through various sources, they are important insofar as each of them, in its own way, justifies the Shīʿī view on ʿAlī's succession after he was murdered in Kufa in the year 40/661. This volume contains two Persian versions-one in verse, the other in prose-of ʿAlī's last will and injunctions addressed to Ḥusayn, the third imam. The original Arabic prose text has come down to us through various ancient sources, the oldest one dating from the fourth/tenth century. The Persian translation in verse was made by the poet Sayyid Ḥasan Ghaznawī (d. 556/1161), the prose version possibly around 910/1504 by a scribe named Muʿīn al-Dīn Munshī Shīrāzi.